Competition Under Credit Rationing: Theory and Evidence from Rural China. - Park, A; Brandt, L; Giles, J (Elsevier, 2003)
We present a duopoly model of financial competition to describe the conditions under which competition leads to greater bank effort when repressed financial systems ration credit. The model features an entrant that freely sets its interest rate, and an incumbent that must charge a rate below that which is market clearing. Both players may exert costly effort to inform themselves about borrower types. Using data on rural financial institutions in China, we test empirically the effects of competition on deposit growth, loan portfolio composition, repayment rates, and other effort measures, finding positive effects of competition on effort and financial performance.